Dr. Danilo Dayag won the best dissertation award in a nationwide search - Dayag, Danilo T. (Animo Repository, 2002)
Dr. Danilo Dayag, chairperson and associate professor of the Department of English and Applied Linguistics (former English Language Education Department) won the Best Dissertation Award in a nationwide search. His DLSU-Manila Ph.D. dissertation in Applied Linguistics defended on November 15, 1999 entitled, Pragmatics of Philippine Print Advertising Discourse.